Synthesis and antibacterial profiling of dehydroamino acid containing argyrin analogues - Yang, Lei (2018)
The argyrins are a family of macrocyclic heptapeptides isolated from the marine myxobacterium Archangium gephyra. Among them, argyrin A 1.1 and B 1.2 displayed potent antibacterial activity against multidrug resistant Gram-negative human pathogen Pseudomonas aeruginosa and Burkholderia multivorans. The bacterial elongation factor G (EF-G) was identified as the conserved cellular target of argyrin A and B in P. aeruginosa.